A Pragma-Stylistic Analysis of Reflections on Death and the Construction of Character Education Values in the Poem Ayā Man Yadda'ī al-Fahm - Aulia, Jihan; Sopian, Asep; Aqwam, Sena Zaeni (Aphorisme: Journal of Arabic Language, Literature, and Education, 2025)
This study aims to identify the forms of imagery, language style, and pragmatic implications in several selected Arabic verses, and to explain the construction of character education values that emerge through the analysis. This research is a qualitative study that employs a content analysis approach. The technique used in this research is documentation. The primary main text is the classic p" poem Ayā poemn Yadda'ī asupplementedd-byith supporting dincludingamelythea the"l-Balāghahlāghah al-W, āandell by various relevant and creative works on stylistic and pragmatic studies. Data were analyzed through Krippendorf's content analysis model, which included unitizing, sampling, coding, reducing, inferring, and narrating. The results of the stu16 stanzas contain bayāni devices in the form of tasybīh, majāz, isti'ārah, and kināyah that are consistently used to affirm moral messages, such as self-awareness of death and prudence in acting in the world. The implications that emerge from the construction of the language style reinforce the message and value of character education about religiosity, humility, and responsibility.